A few Facts About Your Journal - NKO’O AMVENE, Samuel (HEALTH SCIENCES AND DISEASE, 2020)
JOURNAL SCOPE Health Sciences and Disease, is an open source, peer reviewed medical journal that covers all aspects of medicine, pharmacy, biomedical and health sciences, including public health and societal issues. It is an “online first” publication, which means that all the publications articles appear on the website before being included in the print journal. The papers are published in full on the website, with open access. Our vision is to be the leader medical journal in our region. Our mission is to inform and educate all the health professionals and to promote constructive debate on health issues that matter in the management not only of diseases but of health as a whole. Health Sciences and Disease is the official publication of the Faculty of Medicine and Biomedical Sciences of the University of Yaoundé I. Its team is based in Yaounde (Cameroon). Acceptance of manuscripts is based on the originality, the quality of the work and validity of the evidence, the clarity of presentation, and the relevance to our readership. Publications are expected to be concise, well organized and clearly written. Authors submit a manuscript with the understanding that the manuscript (or its essential substance) has not been published other than as an abstract in any language or format and is not currently submitted elsewhere for print or electronic publication. JOURNAL FACTS Publisher Faculty of Medicine and Biomedical Sciences, The University of Yaounde I Editor in chief Samuel Nko’o Amvene, MD Deputy editors • Alfred Kongnyu Njamnshi, MD • Oudou Njoya, MD • Essi Marie-José, Ph.D Technical Secretariat Bediang Georges, Mbede Maguy, Moulion Tapouh Jean Roger, Nko’o Amvene Michael Robert, Belobo Eyebe Grace, Ntsama Ondo Laryssa, Seme Ambroise, Awana Armel, Nko’o Ebale Franklin Albert, Amenele Jeanne Marie Priscille. Advisory Committee Rabiou Cissé (Ouagadougou), Sosso Maurice Aurélien (Yaoundé), Siaka Sidibe (Bamako), Ondo Ndong François (Libreville), Mbacham Wilfred (Yaoundé), Wonkam Ambroise (Cape Town), Zo’o Martin Roger (Le Mans), Mbopi-Keou François Xavier (Yaounde), Ibara JR (Brazzaville), Leke Rose (Yaounde). ISSN (print journal): 1684-2782 EISSN (online) : 2309-6535 INDEXING HSD is indexed by Google Scholar, DOAJ, ROAD, JournalTOCs, African Index Medicus. PubMed and AJOL soon. Health Sciences and Disease home page: http://hsd-fmsb.org Contact information: hsdeditor3@gmail.com. / nkooamvenes@gmail.com Health Sciences and Disease Faculty of Medicine and Biomedical Sciences PO Box 1364, Yaoundé Cameroon. MANUSCRIPT SUBMISSIONS The preferred way for submission is the online submission. Please, refer to the instructions to authors and to the Health Sciences and Disease home page: http://hsd-fmsb.org or to the website of the Faculty of Medicine and Biomedical Sciences http://fmsb-cm.org. Otherwise, manuscripts can be addressed to nkooamvenes@gmail.com. Inquiries about manuscript status and preparation, as well as letters to the editor, should be directed to : Nko’o Amvene Samuel Editor-in-Chief, Health Sciences and Disease Email: nkooamvenes@gmail.com